The Effect of Using the Busuu Application in Teaching to Improve Vocabulary Matery at SMPN 20 Bengkulu City - Nasution, Muhamad Fauzan; Susanto, Ferri; Anita, Anita (The Future of Education Journal, 2026)
Vocabulary mastery is an essential aspect of learning English as it forms the foundation for developing other language skills. However, many students still face difficulties in mastering vocabulary due to unengaging teaching methods and low learning motivation. This study aims to determine the effect of using the Busuu application on students’ vocabulary mastery at SMP Negeri 20 Kota Bengkulu. This research employed a quantitative approach with a quasi-experimental design involving two classes: VII.D as the experimental class and VII.F as the control class, with a total of 62 students. The research instrument was a multiple-choice test administered through pre-test and post-test, and the data were analyzed using SPSS. The results showed that the experimental class experienced a more significant improvement compared to the control class. The mean score of the experimental class increased from 32.77 in the pre-test to 57.65 in the post-test, with score ranges improving from 12–54 to 28–80. Meanwhile, the control class showed an increase from a mean score of 29.77 to 46.19, with score ranges from 13–53 to 20–70. The t-test results revealed a t-value of 3.625 with a significance value of 0.001 (<0.05), indicating a significant difference between the two classes. Furthermore, the ANCOVA results showed an F-value of 44.092 with a significance of 0.001 and a Partial Eta Squared value of 0.599, indicating a strong effect size. In conclusion, the use of the Busuu application is effective in improving students’ vocabulary mastery.